Novel Process Approach for in-situ Insertion of Functional Elements in RTM-Applications - Bobbert, Mathias; Augethaler, Florian; Wang, Zheng; Tröster, Thomas; Meschut, Gerson (Journal of Materials Science Research)
Lightweight design in vehicles leads to an increasing use of fibre-reinforced-plastics (FRP). To ensure the possibility of detachable joints in those constructions specific joining technologies have to be developed. Available technologies are not suitable for mass production or are leading to damage in the FRP. The aim of this paper is to show the possibilities and the general feasibility of a new process approach for the application of functional elements in FRP or hybrid materials during resin transfer moulding (RTM) processes. Therefore the movement of the RTM-tool-punch is utilised to produce an interlock between the splay stud and the fibres of the non-consolidated preform. This enables the application of the elements during the RTM-process. The resin infusion leads to the consolidation of the CFRP and a further fixation of the splay stud. Pull-out-tests as well as torsion tests are showing the mechanical performance of the joints.

The Qurʾānic Cosmology, as an Identity in Itself - Mir Sadri, Seyedeh Saeideh; Tabataba'i, Mohammad Ali (Arabica)

Die Ehe - nur ein Vertrag? Eine islamisch-theologische Perspektive - Tatari, Muna (Ehe in Islam und Christentum)

Gott und Mensch im Spannungsverhältnis von Gerechtigkeit und Barmherzigkeit. Versuch einer islamisch begründeten Positionsbestimmung - Tatari, Muna

Armut und Gerechtigkeit: Christliche und islamische Perspektiven

Der Koran und das Thomasevangelium im Kontext spätantiker Religionsdiskurse - Ghaffar, Zishan (Streit um Jesus. Muslimische und christliche Annäherungen)

Was kann man von Luther heute lernen? Eine muslimische Religionspädagogin, ein evangelischer und ein katholischer Kollege im Gespräch - Kamcili-Yildiz, Naciye; Möller, Rainer; Sajak, Clauß Peter (RelliS. Zeitschrift für den katholischen Religionsunterricht)

Islamic Finance and Ethics - A concise Introduction - Nassery, Idris (In welcher Gesellschaft wollen wir leben? Befunde zu Wirtschaftsethik in der globalisierten Gesellschaft)

Ehe es zu spät ist - die Essentialia und Natur eines islamischen Ehevertrags im Lichte deutscher Rechtsprechung - Nassery, Idris (Ehe im Islam und Christentum)

Shear edge tests: a benchmark in investigating the influence of different surface pretreatment methods on the shear stress of intrinsically manufactured metal-CFRP hybrids - Weidenmann, Kay André; Pottmeyer, Florentin; Wang, Zheng; Tröster, Thomas; Meiners, Dieter; Zinn, Carolin; Schaper, Mirko; Gonzalez, Jonathan Serna (International Journal of Automotive Composites)